2003
DOI: 10.1176/appi.ajp.160.11.1954
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing How One Brain Understands Another: A PET Study of Theory of Mind

Abstract: A language-based TOM task activated distributed brain regions that are important for representing mental states of the self and others, retrieving memory of personal experiences, and coordinating and monitoring the overall performance of the task. The activations in the medial frontal cortex replicate findings in previous TOM studies, while the activations in the cerebellum reinforce the growing evidence that the cerebellum performs cognitive functions in the human brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
92
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(104 citation statements)
references
References 69 publications
(104 reference statements)
10
92
0
2
Order By: Relevance
“…Retrosplenial activation has been reported in many neuroimaging studies of autobiographical memory, many of which also observed greater retrosplenial activation for recent than for remote autobiographical memories (Addis et al, 2004;Andreasen et al, 1995;Burgess et al, 2001;Gilboa et al, 2004;Maguire & Mummery, 1999;Maguire et al, 2000;Piefke et al, 2003). Further, it has been associated with person familiarity , synaesthesia for familiar names (Weiss et al, 2001), emotional processing (Maddock, 1999), "theory of mind" (Calarge et al, 2003), analysis of long-term associations of highly contextual objects (Bar & Aminoff, 2003), and in particular, with spatial and episodic memory (Aggleton & Pearce, 2001;Aggleton et al, 2000;Wiggs et al, 1999). Lesions to the retrosplenial cortex can lead to memory deficits and amnesia, stressing its importance in episodic retrieval (Valenstein et al, 1987).…”
Section: Discussion Autobiographical Memorymentioning
confidence: 93%
“…Retrosplenial activation has been reported in many neuroimaging studies of autobiographical memory, many of which also observed greater retrosplenial activation for recent than for remote autobiographical memories (Addis et al, 2004;Andreasen et al, 1995;Burgess et al, 2001;Gilboa et al, 2004;Maguire & Mummery, 1999;Maguire et al, 2000;Piefke et al, 2003). Further, it has been associated with person familiarity , synaesthesia for familiar names (Weiss et al, 2001), emotional processing (Maddock, 1999), "theory of mind" (Calarge et al, 2003), analysis of long-term associations of highly contextual objects (Bar & Aminoff, 2003), and in particular, with spatial and episodic memory (Aggleton & Pearce, 2001;Aggleton et al, 2000;Wiggs et al, 1999). Lesions to the retrosplenial cortex can lead to memory deficits and amnesia, stressing its importance in episodic retrieval (Valenstein et al, 1987).…”
Section: Discussion Autobiographical Memorymentioning
confidence: 93%
“…Statements reflecting God's anger (-D2) engaged the L MTG, BA 21, a key area in emotional ToM (21,31,32), involved in detection of high-valence emotion in facial expression and linguistic content (21). The same area responds to languageinduced fear (33) and mediates conscious reappraisal of perceived negative emotions (25).…”
Section: Discussionmentioning
confidence: 99%
“…Mr. Pierson is employed by the University of Iowa. His research contribution was also supported by NIH grants (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). He has no other biomedical financial interests relevant to the subject matter of this review.…”
mentioning
confidence: 99%